2022
DOI: 10.1051/ro/2022088
|View full text |Cite
|
Sign up to set email alerts
|

Research on the carbon emission regulation and optimal state of market structure: Based on the perspective of evolutionary game of different stages

Abstract: In the background of green and low-carbon development, many enterprises still have illegal emission behaviors to obtain excess revenue. Therefore, it is an urgent problem to restrain the illegal emission behaviors of enterprises through external supervision. This paper mainly studies the regulatory system composed of government and enterprises. We divide the regulation into two phases: loose regulation and strict regulation, analyzed the impact of government regulatory intensity on carbon emission behavior ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In Equation ( 6), u ij is the membership degree of the j-th sample point belonging to class i. a, b, p represent parameters. Equation (7) is the calculation of sample typical value t ij .…”
Section: Single Factor Evaluation Methods and Comprehensive Evaluatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…In Equation ( 6), u ij is the membership degree of the j-th sample point belonging to class i. a, b, p represent parameters. Equation (7) is the calculation of sample typical value t ij .…”
Section: Single Factor Evaluation Methods and Comprehensive Evaluatio...mentioning
confidence: 99%
“…Although the existing evaluation index system can also measure the development level of townships, the differentiated townships development is an important influencing factor related to their SD [5,6]. Therefore, it is also necessary to develop a more appropriate comprehensive ecological planning system from the actual perspective of each township [7][8][9]. Additionally, corresponding comprehensive evaluations are conducted based on one's own development conditions and level.…”
Section: Introductionmentioning
confidence: 99%
“…Technological innovation is crucial for achieving industrial carbon neutrality because it can improve energy efficiency and promote renewable resources, and its contribution to China's carbon emission reduction is as high as 68.5 % [ 22 ]. An effective market trading mechanism can also promote carbon emission reduction in industry and reduce the economic loss caused by green transformation [ 23 ], which means that ineffective market development can slow down the progress toward industrial carbon neutrality. In recent years, an increasing number of studies have found that market development factors have a greater impact on achieving carbon neutrality [ 24 , 25 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The STIRPAT model is based on the IPAT model, which was revised and proposed by Dietz et al, in 1994. It introduces the mechanism of stochastic impact regression based on the classical IPAT model and combines the estimated indices to analyze the nonhomogeneous relationships among the environmental influences (Sun and Gao, 2022). The STIRPAT model expression is shown in Eq.…”
Section: Patmentioning
confidence: 99%